Railway Bogie Side Frame Strength Analysis - Achdi, Endang; Rizayana, Farid; Septian, Reza Nur (Mestro: Jurnal Teknik Mesin dan Elektro, 2024)
Train is one of the transportations which highly in great demand of people around the world, particularly in Indonesia. The train is expected to be one of the solutions to solve transportation’s problems in Indonesia. Train should fulfill the existing regulation one of them is the structural strengths in resisting static loads that is the loads that can’t change over time, In order to ensure the passengers safety and comfort. The analysis of the train bogie frame begins with gathering the information regarding the model, specification, and formulation of various loading cases, and finite element modeling. The result shows that in the bogie frame, the maximum stress that occurs is 20.5 MPa for the static load category with axial direction. This occurs below the permissible stress of 183.75 MPa. It can be concluded that the stress works below the permitted stress by the material SS400. Therefore, the operation of bogie with static load is in a safe condition.